The political economy of land grabbing - Tim Krieger; Martin Leroch (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2015)
"Land grabbing" or, less emotionally charged, large-scale land acquisitions (LSLA), which occur mainly in the Global South, have become the center of a heated political and academic debate. So far, economists have mostly abstained from this debate. This may possibly be explained by the fact that they view these kind of deals in land property primarily as an opportunity for improved local economic development in poor countries. Arguably, foreign investors are then assumed to be able to utilize arable, but mostly idle land more efficiently than locals (cf., e.g., Deininger/Byerlee, 2011). At the same time, critics (mostly from other disciplines) claim that these very land deals have highly detrimental effects on local populations, especially smallholders, as neither governments nor international investors typically care much about these people's interests and do not honor their often informal land-use rights (cf., e.g., Cotula, 2011). They claim that this may then endanger the local people's livelihoods. [...]
Keywords: 330